2006
DOI: 10.1074/jbc.m600746200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Iodine Induces Caspase-independent Apoptosis in Human Breast Carcinoma Cells Involving the Mitochondria-mediated Pathway

Abstract: Iodine-induced apoptosis was independent of caspases. Iodine dissipated mitochondrial membrane potential, exhibited antioxidant activity, and caused depletion in total cellular thiol content. Western blot results showed a decrease in Bcl-2 and up-regulation of Bax. Immunofluorescence studies confirmed the activation and mitochondrial membrane localization of Bax. Ectopic Bcl-2 overexpression did not rescue iodine-induced cell death. Iodine treatment induces the translocation of apoptosis-inducing factor from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
104
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 53 publications
9
104
1
Order By: Relevance
“…These authors also showed that a caspase inhibitor did not block the apoptotic effect of I 2 , suggesting that caspase pathways were not involved (Shrivastava et al 2006). In the present work, we confirmed the increase in BAX and the nuclear translocation of AIF, but we also detected the activated caspase-7 subunit of 17 kDa, as well as PARP1 cleavage, indicating the possibility that more than one pathway was activated by I 2 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These authors also showed that a caspase inhibitor did not block the apoptotic effect of I 2 , suggesting that caspase pathways were not involved (Shrivastava et al 2006). In the present work, we confirmed the increase in BAX and the nuclear translocation of AIF, but we also detected the activated caspase-7 subunit of 17 kDa, as well as PARP1 cleavage, indicating the possibility that more than one pathway was activated by I 2 .…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have established that at higher concentrations, I 2 can act as a potent free radical; I 2 treatment also causes depletion of thiol levels (Vitale et al 2000, Joanta et al 2006, Shrivastava et al 2006. A shift in the redox state induces retinoblastoma gene (RB) dysfunction and results in a reduced release of E2F-binding factor and G1 cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies suggest the existence of mitochondria or/ and caspases-independent cell death in programmed cell death (PCD). For instance, it has been variously reported that apoptotic pathway was activated by stimuli in a mitochondria-dependent and -independent (MacDonald et al, 1999) or caspase-independent (Kang et al, 2004;Li et al, 2004;Shrivastava et al, 2006;Zhang et al, 2011) or both mitochondria-and caspase-independent manner (Chauhan et al, 2004;Bhalla et al, 2009). Our results showed that Dic did not induced any mitochondrial depolarization and caspase-3 inhibition did not prevent Dic-induced A549 cell death indicating that Dic induced a mitochondria-and caspase-3-independent A549 cell apoptosis (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…In the first case, more than one mechanism or iodine component may be triggered or generated by the iodine/iodide supplement. Several groups have postulated that the antineoplastic I 2 effect could be mediated by direct antioxidant/oxidant action at the mitochondrial level or by the formation of iodolipid intermediates such as 6-IL or iodohexadecanal (Dugrillon et al 1994, Shrivastava et al 2006, Rosner et al 2010. Our group has demonstrated that 6-IL formation in solid tumors (MNU) or cancerous cells (MCF-7) is associated with elevated concentrations of its precursor AA, and that 6-IL formation is independent of peroxidases when the supplement is I 2 (Arroyo- Helguera et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using lung cancer cells (without natural iodine uptake) transfected with the iodide/sodium symporter (NIS) or NIS/TPO, Zhang et al (2003) observed that only in NIS/TPO-transfected cells did excess KI induce apoptosis, indicating that I K from KI needs to be oxidized to have a cytotoxic effect. Data obtained in either in vivo (N-methylnitrosourea (MNU)) or in vitro (the human mammary cancer cell line MCF-7) models of mammary cancer show that I 2 but not I K (KI or NaI) exert an antineoplastic effect by increasing the expression of peroxisome proliferator-activated receptor g (PPARg), which triggers apoptotic mechanisms that include the Bax-caspase and apoptosis-inducing-factor (AIF) pathways (GarcĂ­a-SolĂ­s et al 2005, Shrivastava et al 2006. Moreover, we recently demonstrated that 6-iodolactone (6-IL), which is generated by the iodination of arachidonic acid (AA), is a specific ligand of PPARg (Nuñez-Anita et al 2009).…”
Section: Introductionmentioning
confidence: 99%